Does Eco-Feminism Affect the Quality of ESG Disclosures and Banking Performance? - Sukmawan, Gumilar; Khomsiyah, K. (Golden Ratio of Finance Management, 2024)
This study aims to analyze the relationship between the nature of ecofeminism of female directors and ESG disclosure and the nature of ecofeminism to banking performance. This study uses how many female directors in a bank as an independent variable, while the dependent variable is ESG disclosure and banking performance as measured by ROA. This study uses a sample of conventional banks listed on the Indonesia Stock Exchange from 2021 to 2023. A total of 43 conventional banks were taken as samples, and the purposive sampling method was used. This study used linear regression analysis using IBM SPSS 27. The results of this study found that female directors have no effect on ESG disclosure, while female directors influence banking performance.